Molecular characterization of genus Tor from Indonesia based on 16S rRNA - Rahayu, Dwi Anggorowati; Nugroho, Endik Deni; Azrianingsih, Rodiyati; Kurniawan, Nia (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
Genus Tor is Indonesia's endangered local fish however, the reports on this species from South East Asia is currently limited. This study conducted to characterize molecular genetics and phylogenetic relationship of Tor fish from East Java, West Kalimantan, Padang and North Sumatra from BPBAT Bogor collection using a partial sequence of mtDNA 16S rRNA. A total of ten samples of Genus Tor were collected, then identified based on morphological characters, and the identification was confirmed using molecular data. PCR amplicons at 542 bp in length. The construction of phylogenetic topology was made based on ML and NJ method using Kimura-2 parameter model. Based on the phylogenetic topology showed that Tor fish from Pasuruan are closely related to Tor duoronensis from Padang with a bootstrap value of 66%, while Tor duoronensis fish from North Sumatra and Tor tambra from West Kalimantan are in separated clusters. This finding also contributes to the differentiate Genus Tor from Indonesia based on polymorphic sites